Image Cryptography Based on Chebyshev Polynomials and Transposition- Substitution Transformations - Donia Fadil Chalob; Russul Hussein Hasan; Zainab Mohammed Essa (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
The confirming of security and confidentiality of multimedia data is a serious challenge through the growing dependence on digital communication. This paper offers a new image cryptography based on the Chebyshev chaos polynomials map, via employing the randomness characteristic of chaos concept to improve security. The suggested method includes block shuffling, dynamic offset chaos key production, inter-layer XOR, and block 90 degree rotations to disorder the correlations intrinsic in image. The method is aimed for efficiency and scalability, accomplishing  complexity order for n-pixels over specific cipher rounds. The experiment outcomes depict great resistant to cryptanalysis attacks, containing statistical, differential and brute-force attacks, due to its big key space size and sensitivity to initial values. This algorithm be responsible for a forceful and flexible solution for acquiring secure images, appropriate for high resolution data and real time applications.
Keywords: Multimedia Encryption; Chebyshev Map; Block Scrambling; Real Time Image Cipher; Non-Linear Transformation